Investigação pós-tratamento agudo e crônico com adenosina exógena no nematoide Caenorhabditis elegans - Silva, Thayanara Cruz da (2021)
Adenosine is a purine, which has important biological functions for cell metabolism, in addition to many researches relating its use to neuromodulation. Caenorhabditis elegans is a non-parasitic nematode found in nature in humid environments, and it has many advantages as an alternative experimental model because of its low cost and short duration of tests. Since there is little evidence of a purinergic signaling system (PSS) and of direct purine actions in the worm, regarding its physiology, behaviors and responses to oxidative stress, such a study is necessary. We performed an acute treatment of 1h in liquid medium with final concentrations of 1, 5 and 10 mM of adenosine. We evaluated pharyngeal muscle pumping, defecation rate, morphology, locomotor behavior. We evaluated survival under conditions of stress induced by juglone or thermal heat, levels of the antioxidant enzyme SOD-3 and the localization of the transcription factor DAF-16 (orthologous FOXO in mammals). We also evaluated the formation of reactive oxygen species. Subsequently, a chronic treatment of 38h with adenosine was carried out, in which we observed basic behaviors and levels of SKN-1, gsc-1 and HSP16.2, by quantifying the fluorescence of the GFP reporter protein. Adenosine did not alter the worms' morphology, nor did it interfere with their reproductive behavior. On the other hand, adenosine slows the rate of defecation, pharyngeal pumping, and locomotion, in addition to participating in activating or inhibiting the stress response pathways in C. elegans. Together, these results contribute to the understanding of the physiological and biochemical activity of adenosine in this nematode.